48th AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2012
DOI: 10.2514/6.2012-4304
|View full text |Cite
|
Sign up to set email alerts
|

The "Vortex Reloaded" project: experimental investigation on fully tangential vortex injection in N2O - paraffin hybrid motors

Abstract: This paper deals with an experimental and numerical project intended to study fully tangential vortex injection in a hybrid motor of 1kN class. Due to the knowledge of the CISAS Hybrid Team, the choice for oxidizer has been pressurized nitrous oxide, while paraffin wax has been used as fuel. This investigation follows a previous project where a mixed axial/vortex device has been tested: also if an increase in performance has been observed, a non-uniform grain consumption showed an issue of such device. The wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
(9 reference statements)
0
14
0
Order By: Relevance
“…In a similar fashion to this thesis, the analysis have been validated with the test results provided by an experimental campaign [12]. This research expanded further adding new elements as Liquid Injection [13] [14] and Vortex Injection [15] [16] [17] [18].…”
Section: Computational Fluid Dynamicsmentioning
confidence: 84%
See 1 more Smart Citation
“…In a similar fashion to this thesis, the analysis have been validated with the test results provided by an experimental campaign [12]. This research expanded further adding new elements as Liquid Injection [13] [14] and Vortex Injection [15] [16] [17] [18].…”
Section: Computational Fluid Dynamicsmentioning
confidence: 84%
“…A closer look on the vorticity in the precombustion chamber is given in figure 5. 16, where the plot of the velocity vectors in the plane highlights the hot eddies.…”
Section: Testmentioning
confidence: 99%
“…The 18 tests performed as part of this experiment showed that, as Bellomo said, "…for the regression rate performance parameter the most important factor is the injection type," (Bellomo, et al, 2012). The ANOVA results discussed in Section 4.2…”
Section: Discussionmentioning
confidence: 99%
“…Additional research focusing on the effects of swirl injectors was completed by a group at the University of Padua in Padova, Italy (Bellomo, et al, 2012 (Bellomo, et al, 2012). After an extensive study, consisting of 66 tests, they proposed the following statement.…”
Section: Previous Research On Swirl Injectorsmentioning
confidence: 99%
See 1 more Smart Citation